Developmental trajectories of children's spatial skills: Influencing variables and associations with later mathematical thinking. (October 2021) - Möhring, Wenke; Ribner, Andrew D.; Segerer, Robin; Libertus, Melissa E.; Kahl, Tobias; Troesch, Larissa Maria; Grob, Alexander
Abstract: Few studies have examined the long-term relations between children's early spatial skills and their later mathematical abilities. In the current study, we investigated children's developmental trajectories of spatial skills across four waves from age 3–7 years and their association with children's later mathematical understanding. We assessed children's development in a large, heterogeneous sample of children (N = 586) from diverse cultural backgrounds and mostly low-income homes. Spatial and mathematical skills were measured using standardized assessments. Children's starting points and rate of growth in spatial skills were investigated using latent growth curve models. We explored the influence of various covariates on spatial skill development and found that socioeconomic status, language skills, and sex, but not migration background predicted children's spatial development. Furthermore, our findings showed that children's initial spatial skills––but not their rate of growth––predicted later mathematical understanding, indicating that early spatial reasoning may play a crucial role for learning mathematics. Highlights: Development of spatial skills was assessed longitudinally from age 3–7 years. We explored relations between these paths with children's mathematical skills. Our sample included children from diverse cultural backgrounds and low-SES homes. SES, language skills, and sex predicted children's spatial development. Children's initial spatial skills but not their growth rate predicted mathematics.